4-Methoxyphenyl (E)-3-(Furan-3-yl) Acrylate Inhibits Vascular Smooth Muscle Cell Proliferation. Issue 1 (July 2020) - Han, Seongho; Son, Mina; Lee, Yunmi; Cheon, Sae Hee; Kim, Sung-Whan
Abstract : Abstract: The Cordyceps extract exhibits antiproliferative potential in vascular smooth muscle cells (SMCs) through the mitogen-activated protein kinase signaling pathway. In this study, we aimed to identify the active compounds in the Cordyceps extract and analyze their role in remodeling the arterial wall. On investigation, we discovered the following active compound: 4-methoxyphenyl (E)-3-(furan-3-yl) acrylate and synthesized it. We performed antiproliferation and antimigration assays in addition to an in vivo vessel wall remodeling experiment. Investigation of the mechanism adopted by the active compound to remodel the vessel was performed. The newly synthesized compound inhibited the proliferation and migration of SMCs. Treatment with the synthesized compound reduced neointima formation in the balloon-injured Sprague–Dawley rat model. In addition, this compound inhibited the activation of matrix metalloproteinase-2 and matrix metalloproteinase-9 in type I collagen-activated SMCs. Moreover, this compound suppressed the expression of cycloxygenase-2 (COX-2) in SMCs. Therefore, this compound can exert potential antiarteriosclerotic effects by modulating vessel wall remodeling. In conclusion, the newly synthesized 4-methoxyphenyl ( E )-3-(furan-3-yl) acrylate might be an alternative therapeutic intervention for the treatment of atherosclerosis. Abstract : Supplemental Digital Content is Available in the Text.